Jawapan

2016-01-29T05:39:51+08:00
A. f(x) = 2 /(x-1)

f(x) = y
y = 2 /(x-1)
y(x-1) = 2
xy -y = 2
xy = 2 +y
x = (2 +y) /y

maka, f(x)^-1 = 2+x per x

b. f(x) = 3x /(x-3)

f(x) = y
y = 3x /(x-3)
y(x-3) = 3x
xy -3y = 3x
xy -3x = 3y
x(y-3) = 3y
x = 3y /(y-3)

maka, f(x)^-1 = 3x per x-3

c. f(x) = (2x+4) /(2x-1)

f(x) = y
y = (2x+4) /(2x-1)
y(2x-1) = 2x +4
2xy -y = 2x +4
2xy -2x = y +4
x(2y -2) = y +4
x = (y+4) /(2y-2)

maka, f(x)^-1 = x+4 per 2y-2

d. f(x) = (x+8) /(x-5)

f(x) = y
y = (x+8) /(x-5)
y(x-5) = x +8
xy -5y = x +8
xy -x = 5y +8
x(y-1) = 5y +8
x = (5y+8) /(y-1)

maka, f(x)^-1 = 5x+8 per x-1
1 4 1